ANALISA FAKTOR-FAKTOR YANG MEMPENGARUHI STRUKTUR MODAL PADA PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA - Puji Mega Lestari, 10.05.51.0042 (Students Journal of Economic and Management, 2014)
This study examines the effect of asset structure, profitability, firm size, and business risk to the companys capital structure manufacturing. The population in this study is manufacturing company that is listed on the Indonesia Stock Exchange during the years 2010-2012.Based on the research that has been conducted shows that the asset structure variable has positive and significant impact on the capital structure. Profitability significantly and negatively related to capital structure. Firm size does not affect the companys capital structure. Business risk does not affect the capital structure. Keywords: asset structure, profitability, firm size, business risk, and capital structure